Maternal Barriers in Raising Children with Special Needs in Rural Areas: A Qualitative Study - Cau Kim Jiu; Pitri Pitri; Kharisma Pratama; Usman Usman; Tutur Kardiatun (Indonesian Journal of Disability Studies, 2020)
It is not easy for mothers living in rural areas to raise children with special needs because various obstacles arise from both within and outside the family. This study aimed to explore various obstacles for mothers in raising children with special needs, especially in rural areas. The research design used in this study was descriptive qualitative. The sample in this study consisted of 55 mothers who were selected using purposive sampling method. Data collection was carried out through semi-structured face-to-face interviews and through focus group discussions. The data collected in this study was then analyzed using thematic analysis. There are 3 themes generated in this research including 1) family perception, 2) financials, and 3) access to health care services. Information obtained from this research can provide solutions for families to overcome or get out from the existing barriers and provide information to the government to provide health services to families with children with special needs in rural areas.